In-service training governance, for elementary school teachers in Indonesia - Arwildayanto Arwildayanto; Bambang Budi Wiyono; Rusdinal Rusdinal; Sari Dewi; Varun Ashokan; Eduart Wolok; Hariadi Said (LPMPP Universitas Negeri Yogyakarta, 2023)
This research seeks to explore the governance of in-service training for elementary school teachers so they can be involved in various types, techniques, and training materials. The research design was categorized as mixed methods using both quantitative and qualitative methods. Applied to the concurrent transformative strategy model. The author analyzes perspectives from various frameworks, to get comprehensive results. The finding is that there are still a group of elementary school teachers who have not received in-service training, some have repeatedly received in-service training, and some have even received in-service training more than 5 times. The governance of in-service training in the form of a roadmap has the values of fairness, equity and proportionality in distributing training services to elementary school teachers which are supported by digital-based platforms. So that teachers can easily access, download, document training materials and evidence, and the government as teacher managers can use their track record to assess professionalism and give them the opportunity to become teacher leaders.